Reformulation of General Election Arrangement (Efforts to Avoid Loss of Life among General Election Officers) - Mahmuzar Mahmuzar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
AbstractThe objectives of the current study are to: (1) understand and analyze whether the general election arrangement, stipulated in Law No. 7 of 2017 on General Election, contributed to the deaths of general election officers, particularly voting organizer group (Kelompok Penyelenggara Pemungutan Suara – KPPS) members, during the voting, tallying, and recapitulation stages; (2) to formulate solutions the government should take so that in the following election no general election officers, particularly voting organizer group (KPPS) members, loss their life during the voting, tallying, and recapitulation stages. The current study is normative legal research that requires data in the form of primary legal materials and secondary legal materials obtained through literature study. Once data were collected, they were classified and analyzed in a descriptive manner. Based on the research results, it can be concluded that: (1) the general election arrangement stipulated in Law No. 7 of 2017 on General Election did contribute to the deaths of general election officers, particularly KPPS members, during the voting, tallying, and recapitulation stages on account of excessive work load and lack of rest. As a result, some KPPS members experienced extreme fatigue to a degree in which those who had chronic diseases suffered relapses and ultimately passed away; (2) to avoid loss of general election officers life in future general election, a reformulation of the general election arrangement by lawmakers is necessary through the following process: first, reseparate the implementation of the legislative election and the presidential/vice-presidential election; second, maintain the current simultaneous election with some improvements; third, hold two separate concurrent elections, i.e., concurrent national election and concurrent local election. Out of the three options above, the most plausible alternatives are the second and third since the first option contradicts the ruling of the Constitutional Court. Keywords: avoid, loss of life, general election officers.